1996
DOI: 10.1002/cbm.64
|View full text |Cite
|
Sign up to set email alerts
|

A mental health survey of community correctional clients in Canada

Abstract: SURVEYING THE MENTAL HEALTH OF OFFENDERSNumerous investigations have attempted to determine the magnitude of psychiatric problems among offender samples. This research is usually undertaken for the following reasons. The first is theoretical, in that various attempts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…However, the fact that approximately one fourth of the sample met the criteria for the mental health group and the domestic violence group might suggest that the criteria were too liberal resulting in overinclusive exceptional offender groups. However, numerous studies have examined the incidence of mental health problems, and although the findings vary considerably depending on operational definitions, the percentage of offenders cited with mental health problems in the current study is similar to that of a large-scale population survey of the same jurisdiction (Wormith & McKeague, 1996). Regrettably, the incidence of domestic violence history among adult male offenders has not been thoroughly studied.…”
Section: Limitations and Future Research Needssupporting
confidence: 59%
“…However, the fact that approximately one fourth of the sample met the criteria for the mental health group and the domestic violence group might suggest that the criteria were too liberal resulting in overinclusive exceptional offender groups. However, numerous studies have examined the incidence of mental health problems, and although the findings vary considerably depending on operational definitions, the percentage of offenders cited with mental health problems in the current study is similar to that of a large-scale population survey of the same jurisdiction (Wormith & McKeague, 1996). Regrettably, the incidence of domestic violence history among adult male offenders has not been thoroughly studied.…”
Section: Limitations and Future Research Needssupporting
confidence: 59%
“…The most common disorders found in prison populations of women are substance dependency disorders, with rates of around 30% reported in studies of both convicted (Daniel et al, 1988;Gunn et al, 1991;Maden et al, 1994;Jordan et al, 1996) and remand samples (Andersen et al, 1996;Wormith and McKeague, 1996). Robertson et al (1987), in a Canadian study of a female remand population, reported lower rates for drug dependency/abuse (6%), but rates of alcohol abuse of 34%.…”
Section: Adult Correlates Of Crimementioning
confidence: 94%
“…Probation and Pretrial Services, 2001). Because these probationers often have pronounced needs for various social services (Ditton, 1999;Wormith & McKeague, 1996) and a relatively high risk for recidivism (Council of State Governments, 2002), POs may find it a formidable task to fulfill this challenge while juggling other job requirements.Despite the prevalence of mental health treatment mandates and POs' central role in implementing them, little is known about how POs monitor, encourage, and enforce treatment compliance. In fact, we identified only two lines of research relevant to this issue.…”
mentioning
confidence: 99%
“…Probation and Pretrial Services, 2000;Wormith & McKeague, 1996). Probation officers (POs) have long been responsible for monitoring and enforcing these probationers' compliance with the conditions of probation, which often require probationers to participate in mental health treatment in the community (Ditton, 1999; U.S.…”
mentioning
confidence: 99%